Work-Life Balance of Nurses in Supporting Their Children's Survival Efforts Towards Normal Nutritional Status in Makassar - Nurbaeti; Tutik Agustini; Andi Surahman Batara; Andi Yuliana (Window of Health : Jurnal Kesehatan, 2026)
High workload and dual roles among nurses are associated with reduced Work-Life Balance (WLB), which may negatively affect child survival efforts. Evidence shows that WLB among nurses is generally low to unbalanced, with a prevalence of up to 94.5%, largely influenced by high workloads and excessive working hours (>50 hours/week), and with only a small proportion achieving optimal balance. Therefore, this study aims to examine the relationship between Work Life Balance (WLB) and child survival efforts among nurses (mothers) with children aged 0-12 years, considering work stress, welfare, and family support as key determinants. This study employed an analytical observational design with a cross-sectional approach involving nurses as respondents selected through simple random sampling. Data were collected using structured questionnaires and analyzed using the Spearman correlation test. The results showed that workload was negatively correlated with child Workload Survival Efforts (r = -0.541; p < 0.001) and was the strongest factor associated with reduced WLB. Work stress was negatively associated with WLB (r =-0.365, p = 0.002). In contrast, welfare (r = 0.587; p < 0.001) and family support (r = 0.518; p < 0.001) were positively correlated with child-survival efforts. In conclusion, high workload and work stress reduce WLB, while welfare and family support improve child survival efforts. These findings highlight the importance of institutional strategies, such as workload management, improved welfare policies, and strengthened family support systems, to enhance both nurses’ well-being and child health outcomes.